The influence of rainfall and soil-type distribution on uptake of small grains in semi-arid regions of Zimbabwe: a case of Mberengwa and Zvishavane districts - Mupepi, Oshneck; Matsa, Mark (Elsevier, 2022)
Climate change resulted in farmers shifting from drought intolerant to drought tolerant crops in dry regions of the world. The study assessed the influence of precipitation and soil-type distribution on uptake of small grains in Mberengwa and Zvishavane districts in Zimbabwe. A mixed methods research design was adopted in this study and both qualitative and quantitative research approaches were employed to probe data. Questionnaires, interviews, focus group discussions and observations were used to collect data in this study. Microsoft excel 2013 and Geographic Information System (GIS) were adopted for data analysis in this study. Findings showed that soil type and precipitation distribution have significant influence on uptake of small grains in Mberengwa and Zvishavane Districts. Research findings indicated that perceptions of farmers towards small grain production are determined by precipitation received in the area and the type of soil available. Areas with high precipitation and soils of higher water retention capacity had low uptake of small grains compared to areas with lower precipitation and soils of poor water retention capacity. The study concludes that declining precipitation in arid and semi-arid regions requires adoption of small grains which thrives under dry conditions despite some areas receiving enough precipitation for maize production. The study recommends that organizations or projects that wish to support small grain production in areas of heterogeneous soil type and precipitation distribution focus more on areas of little precipitation and soils of poor moisture retention capacity which do not support large grains to guard against compromising small grain uptake.